Interactional Justice, Leader-Member Exchange, Job Satisfaction: An Internal Marketing Perspective - Dr Zia Khalid; Muhammad Farhan Munir; Dr Ishtiaq Ahmed Malik (Social Science Review Archives, 2025)
Current conceptual work is rooted in internal marketing and Social Exchange Theory (SET) theories. The relationship between interactional justice and leader–member exchange (LMX) is the focus of this research with job satisfaction in the moderating role. Job satisfaction is a central construct in organizational behavior, HRM, and services marketing; having been greatly examined other than the condition shaping leadership processes. Research in the past demonstrates that fair interpersonal treatment by leaders enhances the quality of leader–follower relationships. Existing studies, however, have not discussed employees’ affective evaluations of their work. Employing organizational justice, LMX, and internal marketing literature, present work proposes that job satisfaction can strengthens the positive effects of interactional justice on LMX. It does so by enhancing employees’ willingness to reciprocate fair treatment through high-quality social exchanges. Thus, putting job satisfaction in moderation role this paper advances understanding of justice–exchange dynamics from a new perspective.